The play of law in modern British theatre - Ward, Ian, 1963- (Edinburgh critical studies in law, literature and the humanities., 2021)
This text assesses the credibility of this arresting claim in the immediate context of contemporary British theatre by investigating the place and purpose of law in a range of modern dramatic settings and writings.